Evaluation of Korean Version of the Beliefs about Papanicolau Test and Cervical Cancer in Unmarried University Students - Hae Won Kim; Ga Yeon Ko (Korean Society of Women Health Nursing, 2013)
PURPOSE: This study was conducted to evaluate Korean version of the beliefs about Papanicolau (Pap) test and cervical cancer [CPC-28] in unmarried university students. METHODS: The Korean version of CPC-28 (K-CPC-28) was developed through forward-backward translation techniques. A reliability, confirmatory factor analysis and correlations coefficients were evaluated. Data were collected from 303 unmarried female students attending university using a questionnaire that included28 items of CPC, 5 items of susceptibility of cervicalcancer and 8 items of HPV knowledge. RESULTS: K-CPC-28 had reliable internal consistency with Cronbach's alpha=.74 of six subscales ranged from .66 to .80. Factor loadings of the 28 items of subscales ranged from .31 to .86. Six factors in this study explained 55% of the total variance. In convergent validity of the K-CPC-28, the subscales of K-CPC-28 were significantly correlated with susceptibility scale of cervical cancer and HPV knowledge scale. CONCLUSION: K-CPC-28has satisfactory construct validity and reliability. It seems to be an acceptable tool to assess the attitudes toward cervical cancer prevention and Pap smear in unmarried women. This tool would be also applicable to screen the risk group in cervical cancer prevention and to identify its association with actual Pap test or cervical cancer prevention behaviors.